2007
DOI: 10.1161/circulationaha.106.640573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Health-Related Quality of Life on Long-Term Survival After Cardiac Surgery

Abstract: Background-Health-related quality-of-life instruments have become important measures of early health outcomes after cardiac surgery. The relationship between quality of life after recovery from surgery and subsequent long-term survival has not previously been explored. Our objective was to determine whether the Duke Activity Status Index (DASI) was predictive of subsequent time-related survival after recovery from cardiac surgery. Methods and Results-We examined survival status among 6305 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 44 publications
5
40
0
4
Order By: Relevance
“…The DASI questionnaire is used to evaluate the ability to perform common activities of daily living (higher scores represent better physical functioning), in which each item is weighted by its known metabolic cost. DASI has been commonly used in evaluating patients with cardiovascular diseases [12,26,27,28]. …”
Section: Methodsmentioning
confidence: 99%
“…The DASI questionnaire is used to evaluate the ability to perform common activities of daily living (higher scores represent better physical functioning), in which each item is weighted by its known metabolic cost. DASI has been commonly used in evaluating patients with cardiovascular diseases [12,26,27,28]. …”
Section: Methodsmentioning
confidence: 99%
“…These changes made the items more suitable to Brazilian culture in order to achieve semantic equivalence (between words), idiomatic equivalence (between different idiomatic expressions used in the different cultures), experimental equivalence (words adequate to the cultural context) and conceptual equivalence (validity of the concept explored and events experienced by laypersons) (23,24). Studies have demonstrated that the DASI is correlated with the distance travelled on the Six-Minute Walk Test (r = 0.53) (10), B-type natriuretic peptide levels (r = 0.67) (13), the Canadian Cardiovascular Society Classification (r = 0.58) (7) and patient quality of life and survival (r = 0.64) (11). Moreover, the questionnaire is sensitive to changes in functional status between the preoperative and postoperative periods of cardiovascular surgery (8,12) and a predictor of the ability to return to work (14).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these principles, Hlatky et al (5) created a self-administrated questionnaire denominated the Duke Activity Status Index (DASI) in the United States. This index is employed to predict cardiorespiratory fitness and has been widely used for patients with cardiovascular disease (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional CR, in failing to address such patients' goals, runs the risk that they will "supplement" CR with unsupervised training, risking complications like sternal dehiscence. Alternatively, they may be unable to return to work, with associated reduced quality of life and survival, 9,16 or attempt to return without regaining adequate fitness, risking injury.…”
Section: Discussionmentioning
confidence: 99%